Water user management and financing of irrigation facilities through use of improvement districts - Harrison, Brent, author; Troglin, Todd, author; Kavarian, Mike, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2005)
The Turlock Irrigation District (TID), California's first irrigation district, was established in 1887. The TID owns only the main canals and laterals, which bring irrigation water to large geographical portions of the TID. Improvement districts are organized by local landowners to convey the irrigation water to individual parcels. These local organizations provide essential irrigation service including water conveyance, drainage, and supplemental water from wells and pumps. The cost for these services is paid by assessments levied against the member properties.
Improvement districts
Not digitized by CSUL Digital Services.
Presented during the Third international conference on irrigation and drainage held March 30 - April 2, 2005 in San Diego, California. The theme of the conference was "Water district management and governance."